Effectiveness of Psychoeducation Posters in Improving University Students' Understanding of Digital Burnout - Kartika Cahyaningrum (Indonesian Journal of Educational Studies, 2026)
Abstract. This study aimed to improve university students’ understanding of digital burnout through a digital psychoeducation poster intervention. Digital burnout is a state of physical, mental, and emotional exhaustion resulting from excessive use of digital devices, particularly among Generation Z students who engage in high-intensity online activities. The study commenced with a needs assessment using the Digital Burnout Scale (DBS), administered to 54 students, and in-depth interviews with four respondents who exhibited high levels of digital burnout. The needs assessment revealed that the majority of students fell in the moderate digital burnout category (62.96%), while interviews disclosed physical complaints (headaches, eye strain, muscle pain) and psychological symptoms (anxiety, difficulty concentrating, digital dependency). Based on these findings, a psychoeducation poster themed “Easy Habits to Stay Calm Online” was developed and disseminated via Instagram. A total of 69 respondents completed pre-test and post-test evaluations. Results indicated a substantial increase in understanding: only 13% of respondents demonstrated comprehension of digital burnout on the pre-test, whereas 90% reported understanding after viewing the poster. These findings demonstrate that poster-based media constitute an effective, concise, and accessible health promotion tool for increasing students’ knowledge of digital burnout and encouraging healthier technology use behaviors. Keywords: digital burnout; psychoeducation; university students